Investigation of Plastic Behavior of Alloyed Steel Deformed during Martensitic Transformation - Kandrotaitė-Janutienė, R.; Baltušnikas, A. (Проблемы прочности, 2016)
We present the investigation of permanent strain of steel specimen occurred when metallurgical transformations take place even under small stress applied externally lower than the yield stress of material. Three alloyed steel grades were investigated: THG2000 (Uddeholm, Sweden), 40Kh13 and 95Kh18 (GOST, Russia). All steel grades differ in carbon content and amount of alloying elements and behave differently when transformation occurs. This intensively increased plasticity of steel specimen was observed during bending test when bending stress was just 100 MPa and was less than 10% of yield strength of the steel. The steel specimens were heated to 900–1050°C temperature and then bent during air quenching. Plastic deflections were observed though all cooling process that involved martensitic transformation as well. Different effect of compression and tensile stresses on microstructure evolution during martensitic transformation was determined by X-ray analysis as both types of stresses were formed in bent specimens. Исследованы пластические деформации, возникающие в стальных образцах вследствие микроструктурных трансформаций при воздействии внешних нагрузок, уровень которых может не достигать предела текучести материала. Рассматривались три легированные стали THG200 (производитель Уддехольм, Швеция), 40Х13 и 95Х18 (Россия) с разными легирующими элементами и процентным содержанием углерода, а также поведением при микроструктурных трансформациях. При генерировании изгибных напряжений порядка 100 МПа, не превышающих 10% предела текучести сталей, наблюдается возникновение пластических зон в стальных образцах, которые подвергались предварительному нагреву до 900 1050°С и последующему изгибу при закалке на воздухе. Пластические деформации возникали при реализации всех режимов охлаждения, которые сопровождались мартенситным превращением. С помощью рентгенографических исследований было выявлено разное влияние растягивающих и сжимающих изгибных напряжений на микроструктурные изменения при мартенситных превращениях. Досліджено пластичні деформації, що виникають у стальних зразках внаслідок мікроструктурних трансформацій при дії зовнішніх навантажень, рівень яких може не досягати границі плинності матеріалу. Розглядалися три леговані сталі ТHG200 (виробник Уддехольм, Швеція), 40Х13 та 95Х18 (Росія) з різними легованими елементами і процентним вмістом вуглецю та поведінкою при мікроструктурних трансформаціях. При генеруванні згинальних напружень порядку 100 МПа, що не перевищу є 10% границі плинності сталей, має місце виникнення пластичних зон у стальних зразках, які піддавали попередньому нагріванню до 900 1050°С і наступному згину при загартуванні на повітрі. Пластичні деформації виникали за реалізації всіх режимів охолодження, які супроводжувалися мартенситним перетворенням. За допомогою рентгенографічних досліджень виявлено різний вплив розтяжних і стискальних згинних напружень на мікроструктурні зміни при мартенситних перетвореннях.